Protein A chromatography in monoclonal antibody purification - Curtis, Michael (Kansas State University, 2018)
The bio-pharmaceutical industry began over 30 years ago with the production of human insulin and has shown incredible growth ever since. With forecasted annual worldwide sales of over $450B in 2025 for biopharmaceuticals, they are expected to be at least 25% of the entire pharmaceutical market. Therapeutics based on monoclonal antibodies (mAbs) make up roughly a third of all biopharmaceutical sales with indications from asthma, to cancer, to Parkinson’s disease. The recent approval of the first biosimilar mAb products in the US and Europe has exposed up to 20 of the top grossing biologic products to competition for the first time, while 75% of the US market is expected to lose patent exclusivity by 2020. With the increased competition from biosimilars, the costs associated with producing mAb based therapeutics will be a constraint on maintaining market share going forward. The majority of the total manufacturing costs for mAbs resides in the downstream processing where Protein A chromatography is the predominantly employed technology for the primary capture step. With Protein A’s high unit cost of up to $15,000 per liter and susceptibility to deamidification when exposed to high pH cleaning and sanitization chemicals, it is no surprise that many mAb manufacturers are considering alternatives. The objective of this work is to review the production process of mAb therapeutics, with a specific focus on the advantages, disadvantages, and alternatives to Protein A affinity chromatography as the primary capture step in downstream processing.
Keywords: mAb; Protein A; Chromatography; antibody